2003
DOI: 10.1029/2002jb002375
|View full text |Cite
|
Sign up to set email alerts
|

Fault interaction and stress triggering of twentieth century earthquakes in Mongolia

Abstract: [1] A cluster of exceptionally large earthquakes in the interior of Asia occurred from 1905 to 1967: the 1905 M7.9 Tsetserleg and M8.4 Bolnai earthquakes, the 1931 M8.0 Fu Yun earthquake, the 1957 M8.1 Gobi-Altai earthquake, and the 1967 M7.1 Mogod earthquake (sequence). Each of the larger (M ! 8) earthquakes involved strike-slip faulting averaging more than 5 m and rupture lengths of several hundred kilometers. Available geologic data indicate that recurrence intervals on the major source faults are several t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 62 publications
3
57
0
2
Order By: Relevance
“…Our goal was to study a whole series of events and, taking the time delays into account, we considered the visco-elastic postseismic response important in the SISZ. Similar studies that span nearly or more than a century were published by Pollitz et al (2003Pollitz et al ( , 2004.…”
Section: Introductionsupporting
confidence: 49%
“…Our goal was to study a whole series of events and, taking the time delays into account, we considered the visco-elastic postseismic response important in the SISZ. Similar studies that span nearly or more than a century were published by Pollitz et al (2003Pollitz et al ( , 2004.…”
Section: Introductionsupporting
confidence: 49%
“…This observation raises the questions of whether large earthquakes may have triggered other large earthquakes in an apparently dormant zone, even if faults are separated by several hundred kilometers, and what physical parameters control fault behaviors. The idea of earthquake clusters in Mongolia has already been explored by numerical modeling of postseismic stress relaxation of the lithosphere after large earthquakes (Chéry et al, 2001;Pollitz et al, 2003). These articles show that viscoelastic and elastic stress transfer could be responsible for earthquake time clustering, on timescales of decades, along continental faults separated by hundreds kilometers.…”
Section: Discussionmentioning
confidence: 99%
“…1a). Considering the high rate of large earthquakes between 1905 and 1957, these earthquakes have been described as a seismic cluster involving mechanical coupling between faults (Chéry et al, 2001;Pollitz et al, 2003;Vergnolle et al, 2003). These earthquakes occurred along strike-slip faults that are several hundred kilometers long (i.e., Tsetserleg, Bolnay, Fuyun, and Bogd faults) and accommodate the northernmost deformation related to the India-Asia collision (Florensov and Solonenko, 1965;Molnar and Tapponnier, 1977;Tapponnier and Molnar, 1979;Cunningham, 1998).…”
Section: Introduction and Tectonic Settingmentioning
confidence: 99%
“…We compare our results with thermobarometric and petrologic analysis of lower crustal and mantle xenoliths in central Mongolia, with seismic tomography results and with gravity modeling applied to this region. In the companion paper, Pollitz et al [2003] use the viscosities found here in order to investigate stress transfer trough viscoelastic relaxation in an attempt to explain the clustering of large earthquakes in Mongolia in this century…”
Section: Introductionmentioning
confidence: 99%